Comparative Antifungal Study of Essential Oil with Allopathic Drugs against Malassezia furfur - Sharma, Richa (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT The present study aim to evaluate the potential inhibitory effect of Curcuma longa (turmeric) oil on lipophilic, yeast like fungus Malassezia furfur which causes Pityriasis versicolor disease, a common superficial fungal skin disease. The antifungal activity of turmeric oil was screened by using disc diffusion method and microdilution method. Results indicated that, in screening of turmeric oil by disc diffusion method, the diameter of inhibition zone was found to be 55 mm which was greater than the inhibiton zone of reference antibiotics i.e streptomycin and gentamycin of 17 mm and 16.5 mm respectively. By using microdilution method, the Minimum inhibitory concentration (MIC) of turmeric oil was found to be 0.1Âµl/ml against Malassezia furfur. These findings provide promising information for the potential use of Curcuma longa (turmeric) oil as a traditional herbal medicine for the treatment of Pityriasis versicolor disease.